Carrageenan catabolism is encoded by a complex regulon in marine heterotrophic bacteria. Issue 1 (December 2017) - Ficko-Blean, Elizabeth; Préchoux, Aurélie; Thomas, François; Rochat, Tatiana; Larocque, Robert; Zhu, Yongtao; Stam, Mark; Génicot, Sabine; Jam, Murielle; Calteau, Alexandra; Viart, Benjamin; Ropartz, David; et al.
Abstract Macroalgae contribute substantially to primary production in coastal ecosystems. Their biomass, mainly consisting of polysaccharides, is cycled into the environment by marine heterotrophic bacteria using largely uncharacterized mechanisms. Here we describe the complete catabolic pathway for carrageenans, major cell wall polysaccharides of red macroalgae, in the marine heterotrophic bacteriumZobellia galactanivorans . Carrageenan catabolism relies on a multifaceted carrageenan-induced regulon, including a non-canonical polysaccharide utilization locus (PUL) and genes distal to the PUL, including asusCD -like pair. The carrageenan utilization system is well conserved in marineBacteroidetes but modified in other phyla of marine heterotrophic bacteria. The core system is completed by additional functions that might be assumed by non-orthologous genes in different species. This complex genetic structure may be the result of multiple evolutionary events including gene duplications and horizontal gene transfers. These results allow for an extension on the definition of bacterial PUL-mediated polysaccharide digestion. Carrageenans, major cell wall polysaccharides of red macroalgae, are metabolised by marine heterotrophic bacteria through unclear mechanisms. Here, the authors identify an unusual polysaccharide-utilization locus encoding carrageenan catabolism in a marine bacterium, and characterise the complete pathway.